Pengaruh Management Resources DPMPD Terhadap Keberhasilan Pelaksanaan Program Pemberdayaan Masyarakat di Kabupaten Kediri Masa Pandemi Covid-19 - Moh Hamzah Fansuri; Sutinah Sutinah; Septi Ariadi (Jurnal Sosiologi Andalas, 2023)
The purpose of this study focuses on the influence of the level of DPMPD resource management on the successful implementation of community empowerment programs in Kediri Regency during the Covid-19 pandemic where the background of the pandemic is changing the system and empowerment that demands resource management to continue to empower the community in Kediri Regency. This study uses a quantitative approach that uses data collection techniques with questionnaires (Likert scale), observation, interviews, and documentation. Sampling in this study used a random sampling technique to DPMPD employees and participants who took part in the training. The results of the analysis of the influence of DPMPD management resources on the successful implementation of community empowerment programs in Kediri Regency during the Covid-19 pandemic showed a significance level of 0.00 and R square of 0.659 and the equation value which showed a positive value so that it could be interpreted that there was a significant and positive influence. resource management on the success of the implementation of the empowerment program that is equal to 65.9%.